2019
DOI: 10.1088/1742-6596/1398/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of selected parameters of concrete composite containing recyclate obtained from fire-resistant cullet

Abstract: The purpose of the work is to determine the possibility of using waste from waste heat-resistant cullet as a filler in concrete composites. The article discusses the results of testing selected performance properties of the designed concrete composite. The samples were tested for mechanical properties: compressive strength, impact resistance. Research also included identifying structural changes in the designed composite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Research of available literature has shown that if cement is replaced by cullet, after 28 days of curing concrete composite has a lowered compressive strength as compared to reference concrete. On the other hand, after 90 and 180 days of curing a much smaller impact of the presence of cullet is observed on lowering the strength of composites [1]. This proves the pozzolanic reactivity of cullet [35], which is correlated with the average compressive strength.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Research of available literature has shown that if cement is replaced by cullet, after 28 days of curing concrete composite has a lowered compressive strength as compared to reference concrete. On the other hand, after 90 and 180 days of curing a much smaller impact of the presence of cullet is observed on lowering the strength of composites [1]. This proves the pozzolanic reactivity of cullet [35], which is correlated with the average compressive strength.…”
Section: Introductionmentioning
confidence: 70%
“…The first disquieting phenomenon is the generation of all types of waste, and the second one is the depletion of natural resources. Both phenomena require global attention to allow innovative and sustainable applications being worked out [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glass used for the production of concrete needs to undergo a special processing procedure [ 5 , 11 ]. The whole material may be recycled.…”
Section: Introductionmentioning
confidence: 99%
“…A review of published research [ 5 , 11 ] has shown that no analyses have been implemented yet with respect to recycling of used up heat resistant dishes for the production of concrete. While conducting the research, the authors took into account the feasibility of using glass recyclate as an optional supplementing aggregate for the production of cement composites exposed to thermal loads.…”
Section: Introductionmentioning
confidence: 99%